(untitled) (Journal of Industrial and Mechanical Engineering, 2025)
This study explores the evolution from industry 4.0 to industry 5.0, where digitalization and automation move towards a more human approach, highlighting that it is not a substitution, but a synergistic integration. Industry 5.0 emphasizes human-machine collaboration, redefining the role of people in industry by combining human creativity and judgment with the precision of machines. The need to redefine technologies to respond to new social demands is highlighted, promoting a balanced human-machine integration. This approach seeks to maximize productive efficiency without neglecting the quality of life. The transition is described as a hybrid where advanced technologies and human centrality coexist, creating more resilient, circular and socially oriented systems. In addition, challenges and opportunities faced by companies, especially SMEs, in reconfiguring their processes and adopting new technologies are examined.